A Comparative Assessment of Emerging Solvents and Adsorbents for Mitigating CO2 Emissions From the Industrial Sector by Using Molecular Modeling Tools - Bahamon, Daniel; Alkhatib, Ismail I. I.; Alkhatib, Nour; Builes, Santiago; Sinnokrot, Mutasem; Vega, Lourdes F. (Frontiers in Energy Research, 2020)
The possibilities offered by molecular modeling tools to obtain relevant data at process conditions, while also gaining molecular insights on the techniques used for CO2 capture and separation, are presented here using selected case studies. Two different technologies, absorption with amine-based systems and adsorption on porous materials, were explored, using the molecular-based equation of state, soft-Statistical Associating Fluid Theory (SAFT), and Grand Canonical Monte Carlo simulations, respectively. The aqueous monoethanolamine (MEA) system was set as the benchmark for absorption and compared to the performance of 8 alternative amine-based systems, while 16 adsorbents belonging to different families (zeolites, metal–organic frameworks, amorphous silicas, and activated carbons), bare or functionalized with alkylamines, were investigated for the separation of CO2 by adsorption. In addition to obtaining molecular information on the CO2 capture process, the models were further used to examine the CO2 capture performance in terms of cyclic working capacity and energy index as key performance indicators, allowing the identification of promising systems that can improve the current ones to be further evaluated for separation in non-power industries. Results show that for the same total amine mass concentration, non-aqueous amine solvents have a 5–10% reduction in cyclic working capacity, and a 10–30% decrease in the energy index compared to their aqueous counterparts due to their lower heat of vaporization and specific heat capacity. In addition, M-MOF-74, NaX, and NaY structures present the best results for adsorption in temperature swing adsorption (TSA) processes. Similar values of energy requirements to those of amine-based systems (2–2.5 MJ kg CO2–1) were obtained for some of the adsorbent; however, the disadvantage of the TSA process versus absorption should be considered. These results confirm the reliability of molecular modeling as an attractive and valuable screening tool for CO2 capture and separation processes.